Researchon variable area hybrid system using optimized FractionalOrderControl andPassivity-BasedControl. (January 2017) - Chandrasekar, Priya; Ponnusamy, Lakshmi
Highlights: Designing a controller for a hybrid system is the research topic of interest. The combination of spherical conical interacting tank hybrid system is taken for study. To demonstrate the applicability of hybrid PSOGSA tuned Fractional Order Controller and Passivity-Based Controller for the hybrid system. To simulate the control algorithms in MATLAB and implement in real time using LABVIEW. Comparison of performance of servo and regulatory response. Abstract: Fractional Order (FO) calculus has been gaining increasing attention in research communities. Additionally, the concept of passivity for nonlinear systems has attracted new interest in nonlinear system control. This work aims to develop a hybrid PSOGSA-based Proportional Integral (PI), FO and Passivity Based Controller (PBCr) for a variable area hybrid system, namely, spherical–conical interacting tank system. A computer based control system is developed with data acquisition, processing/computation and for the generation of outputs. A real time model of the hybrid system is obtained experimentally. The controller response is obtained in MATLAB simulation and in real time through LABVIEW software and the performance of the controllers is compared in terms of error criteria. The results show that hybrid PSOGSA optimized PBCr works comparatively efficiently, with improved performance. Graphical abstract: